Implications of Media Capture on Editorial Freedom Tanzania: A Comparative Study of Mwananchi And Habari Leo - Lucas Nyakibai,; Dotto Bulendu,; Peter C. Mataba,; Dietrick Kaijanangoma, (Technium Social Sciences Journal, 2026)
This study examined the implications of media capture on editorial freedom in Tanzania: a comparative study of Mwananchi and Habari Leo newspapers. The study examined how media ownership affects journalistic independence in Mwananchi and Habari Leo newspapers, assessed the regulatory implications on editorial freedom in Mwananchi and Habari Leo newspapers, assessed the political influence on editorial decision making Mwananchi and Habari Leo newspapers and analyzed framing of news by these two newspapers. A qualitative research approach with descriptive design were applied, integrating semi-structured interviews and content analysis to compare for sematic analysis of media capture between private owned (Mwananchi) and state-owned (Habari Leo) newspapers. Using purposive sampling technique this study interviewed 10 participants and analysed a total of 154 newspaper issues published from 1st June to November 30, 2024. The findings revealed that study found that ownership structure affects journalistic independence. However, Mwananchi was free from owners influence in decision-making comparing to Habari Leo which faced direct and indirect influence due to its nature of ownership. The findings discovered that laws and regulation had both positive and negative impacts to the media by ensuring adherence to media ethics, protecting individuals from harm and prohibiting non-journalists from working in media, while other laws were seen as they undermined editorial freedom. It was also indicated that political influence affected editorial freedom and independence in decision making. Lastly, the findings revealed that Habari Leo, that ownership structures shaped how the selected media outlets framed news. The findings are of great importance for media industry in Tanzania, policy and scholars as they portray the current state of media capture and its implications to editorial freedom in Tanzania. This study is valuable for media houses seeking to improve their editorial freedom and independence.